Scaffolding Technique on Students’ Ability to Write An Essay - Silvia Melati Sukma; Yanti Suryanti; Lungguh Halira Vonti (FKIP UNIVERSITAS PAKUAN, 2021)
Writing is a difficult skill to be taught. Students have problems especially in essay writing. They feel afraid to write their ideas and make errors and mistakes. This research aimed to find out the use of scaffolding techniques on students’ ability to write an essay. The research was conducted at the English Language Education Study Program of Teacher Training and Educational Sciences, Pakuan University. There are 12 students from fourth semester as the participants. In this research, pre-experimental methods with one group pre-test and post-test designs are used. Written test is given to measure students’ ability to write an essay. The data are analysed using the t-test formula. According to the data analysis, the mean of the difference was 19,75. Furthermore, the t-test value is 7,78. Meanwhile, t-table value is 2,20 at significant level 0,05 with degree of freedom (df) is 11. It shows that the t-test value is higher than the t-table value (7,78 more than 2,20). It means that an alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. In conclusion, the result shows that scaffolding technique is effective to be applied.